Implementation of Sensitive Interventions in Efforts to Prevent Stunting of Toddlers in Sigaol Simbolon Village, Palipi District, Samosir Regency in 2023 - Elya Nora Girsang; Sonny P. Warouw; Rahmad Alyakin Dakbi; Mido Ester Sitorus; Frida Lina Tarigan (Jurnal Info Sains : Informatika dan Sains, 2023)
This study explains the implementation of sensitive intervention policies in handling stunting in Sigaol Simbolon Village referring to Samosir Regent Regulation No. 67 of 2022 concerning the Acceleration of Stunting Reduction in Samosir Regency. The research was conducted in Sigaol Simbolon village. This study aims: To determine the implementation of sensitive interventions in efforts to prevent stunting in toddlers in Sigaol Simbolon Village, Palipi District, Samosir Regency in 2023. This research uses descriptive methods and qualitative approaches. Informants in this study were used with purposive techniques, consisting of: Village Head, Village Officials, Chairman of TP-PKK, Village Midwives, and Masyarat Data obtained from research results through literature studies and field studies, namely, documentation and interviews conducted with informants. The results of this study The implementation of interventions in households that use access to clean water is quite good, the implementation of interventions in households that use access to sanitation has not been optimal, The implementation of interventions for assisting families at risk of stunting has run optimally, The implementation of interventions for poor and vulnerable families who receive conditional cash transfers has not been optimal, The implementation of interventions in Contribution Assistance Recipients (PBI) of National Health Insurance has been Optimal. Conclusions and Suggestions: it is necessary to increase the activities of sensitive intervention services in all services by communicating effectively both to the stunting acceleration team, as well as to the community so as to achieve a reduction in stunting prevalence in Sigaol Simbolon village.